2021
DOI: 10.1515/chem-2021-0072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mica mineral on flame retardancy and mechanical properties of intumescent flame retardant polypropylene composites

Abstract: In many plastic applications, improvement of the flame retardancy is a very significant topic. Polypropylene (PP) is used in many applications such as housing industry due to its cost performance efficiency. Enhancement of flame retardancy properties of PP is necessary in many applications. In this study, the investigation focuses on the synergistic effect of mica mineral and IFR in enhancing the flame retardancy properties of PP in order to achieve cost competitive solution, so as to provide that different/va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Therefore, it is of great significance to improve the fire resistance of PP to reduce fire hazards and guarantee people's life safety. [1][2][3][4] Numerous flame retardants (FR) have been developed for PP, mainly including bromine-based, [5,6] nitrogen-based, [7,8] phosphorous-based, [9,10] silicon-based, [11,12] and sulfur-based [13] as well as various compound elements. Halogen flame retardants represented by bromine-based FR have good compatibility with the PP material so that it will not significantly affect the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to improve the fire resistance of PP to reduce fire hazards and guarantee people's life safety. [1][2][3][4] Numerous flame retardants (FR) have been developed for PP, mainly including bromine-based, [5,6] nitrogen-based, [7,8] phosphorous-based, [9,10] silicon-based, [11,12] and sulfur-based [13] as well as various compound elements. Halogen flame retardants represented by bromine-based FR have good compatibility with the PP material so that it will not significantly affect the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have been conducted to enhance the efficacy of different IFR systems for PP by utilizing various compounds in different ratios 38–40 . Some fillers such as zinc borate, montmorillonite, expanded graphite, sepiolite, clay, calcium carbonate, nickel‐aluminum hydrotalcite, boric acid, mica, and strontium carbonate have been used to reinforce the char layer formed by IFR system, thereby enhancing the thermal/fire resistances of the composites and smoke suppression 41–50 . Furthermore, some improvements in mechanical properties were also reported with the addition of the fillers.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nanomaterials can make up for these disadvantages . Bao, Ali, and Kahraman studied the influence of different nanomaterials on IFR, and all concluded that nanomaterials and IFR have a good synergistic flame retardant effect. Nano-silica is a nanomaterial with good antioxidation properties, which can be used in the preparation of anticorrosion coatings .…”
Section: Introductionmentioning
confidence: 99%